Zygoparity and sex steroid hormone profiles in bluemouth Helicolenus dactylopterus. Issue 5 (21st March 2017) - Sequeira, V.; Couto, E.; Neves, A.; Vieira, A. R.; Paiva, R. B.; Canario, A. V. M.; Gordo, L. S.
Abstract : Two hundred and seven individuals (103 females and 104 males) of bluemouth Helicolenus dactylopterus (Scorpaeniformes, Sebastidae), a commercially important deep‐water species with an unusual reproductive strategy, from the eastern Atlantic Ocean ranging from 13·9 to 37·5 cm total length ( L T ) were analysed from September 2011 to October 2012. The analysis included gonad maturity phases and blood‐plasma levels of oestradiol‐17β (E2 ), 11‐ketotestosterone (11‐KT) and 17, 20β‐dihydroxypregn‐4‐en‐3‐one (17, 20β‐P). Results confirmed the existence of an annual reproductive cycle with asynchrony between females and males and a spawning season from January to May. A pronounced peak in 17, 20β‐P in October for both sexes was associated with possible mating behaviour and recent copula. Levels of E2 increased preceding the elevation of the gonado‐somatic index during ovarian growth and were lower during regression and regeneration. The frequency distribution of oocyte–embryonic stages and variation of hormone levels suggest the existence of daily rhythms. Fertilization was detected between 2000–0000 and 0800–1200 h and spawning took place throughout the day peaking between 2000 and 0000 h. The cyclic pattern of sex steroids and ovarian recruitment provides a new insight into the reproductive strategy of this species.